Benefits of an open access echocardiography service: a Dutch prospective cohort study - van Gurp, N. (Bohn Stafleu van Loghum, 2013)
BACKGROUND: Open access echocardiography has been evaluated in the United Kingdom, but hardly in the Netherlands. The echocardiography service of the SHL-Groep in Etten-Leur was set up independently from the regional hospitals. Cardiologists not involved in the direct care of the participating patients evaluated the echocardiograms taken by ultrasound technicians. AIMS: We estimated the reduction in the number of referrals to regional cardiologists, the adherence of the general practitioners (GPs) to the advice of the evaluating cardiologist, GPs’ opinion on the benefit of the echocardiography service and GPs’ adherence to the diagnostic protocol advocated in the Dutch clinical guideline for heart failure. METHODS: A prospective cohort study was performed. Patients were included from April 2011 to April 2012 (N = 155). Data from application forms (N = 155), echocardiography results (N = 155) and telephone interviews with GPs (N = 138) were analysed. RESULTS: GPs referred less patients to the cardiologist than they would have done without echocardiography available (92 % vs. 34 %, p < 0.001). They treated more patients by themselves (62 % vs. 10 %, p < 0.001). Most GPs (81 %) followed the advice presented on the echocardiogram result. Most GPs (82 %) found the service had clinical benefit for the patient. Sixty two percent of echocardiography requests met the criteria of the Dutch clinical guideline for heart failure. CONCLUSION: Open access echocardiography saved referrals to the cardiology department, saved time, and enabled GPs to treat more patients by themselves. Adherence to diagnostic guidelines for heart failure was suboptimal.